Review and analysis of damage and existing systems of protecting tower cranes under the influence of a blast wave - Gorbatyuk, Y.; Bulavka, O.; Горбатюк, Євген Володимирович; Булавка, Олег Олександрович (Харківський національний автомобільно-дорожній університет, 2023)
The problem of assessing the technical condition of stationary tower cranes of various types by expert organizations in order to determine the possibility of their further operation and the methods of capital repair is relevant. At the same time, one should take into account the nature of the consequences of damage to metal structures and the type of repair, if it is at all possible. The topic of the article is of a practical nature. An attempt was made to have an initial representation and visual analysis of the condition of different types of tower cranes under the conditions of explosive air shock waves depending on the distance to the cranes. The article attempts to substantiate the consequences of the destruction of metal structures, mechanisms or protection systems and to point out some regularities that require close attention during the operation of tower cranes and their further research. Goal. The purpose of the work was to make a damage survey of the different types of tower cranes that have been damaged and their existing protection systems and to provide assumptions for further research on the stability of tower cranes in the conditions of air shock waves. Methodology. The approaches adopted in the work to solve the set goal are based on the conditional division into categories of damage to stationary tower cranes under the action of air shock waves. The results. The analysis of damage to tower cranes will make it possible to take into account in the future the development of typical projects in accordance with the technical documentation regarding their disassembly-assembly, types of repairs, etc. Originality. The study of the stability of tower cranes under the conditions of air shock waves is a rare and specific direction in the field of engineering research. Therefore, the results of this study will fill the gaps in scientific literature and engineering practice. Practical meaning. The results of the study can lead to the development of new approaches and recommendations for the design of tower cranes taking into account possible air shock waves. This will allow engineers to create safer and more reliable designs for working in hazardous environments.
Огляд і аналіз пошкоджень та існуючих систем захисту баштових кранів під впливом вибухової хвилі
Keywords: damage; tower cranes; blast wave; air blast; restoration; operation; ураження; баштові крани; вибухова хвиля; повітряна ударна хвиля; відновлення; експлуатація; 621.873; 10.30977/AT.2219-8342.2023.53.0.02